Financial Factors That Reduce Financial Distress in The Manufacturing Industry - Octaviany, Lidya; Ratnasari, Martdian (Jurnal Akuntansi dan Bisnis, 2024)
This research is motivated by the limited literature that discusses financial factors that can reduce financial distress in manufacturing companies in Indonesia, so it aims to find out what financial factors have an influence in reducing financial distress using the basis of observations of 31 companies over 5 years (2018-2022) with a total of 155 samples. This research uses 1 dependent variable, namely Decrease in Financial Distress (difference in FD per year) and 4 independent variables, namely profitability (ROA), liquidity (CR), leverage (DAR), sales growth (SG). The research method used is multiple linear regression to find out the influence of each independent variable on the existing dependent variable. The results of this research show that profitability and liquidity have a positive effect in reducing financial distress, while leverage and sales growth have no effect in reducing financial distress. Apart from that, this research also proves that there is a decrease in financial distress in manufacturing companies in Indonesia for the 2018-2022 period. Therefore, from the results of existing research, there are several solutions that can be implemented by companies to reduce company financial distress, namely by optimizing the use of resources, reducing short-term debt, and optimizing the use of current assets as well as maintaining sufficient cash levels to ensure the company can meet its short-term obligations.